Spiritual Intelligence of High School Students in Relation to Gender, Family and Locality - K. , Revathi; H. , Deepa (International Journal of Psychosocial Rehabilitation, 2020)
Spiritual intelligence is the ability to behave with wisdom and compassion while maintaining inner and outer peace, regardless of the situation, which means to become more fully human. And also, it is the expression of innate spiritual qualities through our thoughts, actions, and attitudes. The present study is about the spiritual intelligence of high school students in relation to gender, family, and locality. This test to measure the inventory of spiritual intelligence constructed and evaluated by the investigator was administered using a simple random technique to 549 high school students. This study reveals that students have average levels.